Zanthoxylum alatum Roxb. seed extract ameliorates stress aggravated DSS-induced ulcerative colitis in mice: Plausible role on NF-κB signaling axis. (28th October 2021) - Kalyankumarraju, Malayamarutham; Puppala, Eswara Rao; Ahmed, Sahabuddin; Jagadeesh Kumar, Gangasani; Tene, Kalyani; N P, Syamprasad; Sahu, Bidya Dhar; Barua, Chandana Choudhury; Naidu, V.G.M.
Abstract: Ethnopharmacological relevance: Zanthoxylum alatum (ZA) Roxb (family: Rutaceae) plant has been traditionally used for multiple indications by local healers among different communities of South Asian countries mainly in India and Bangladesh. The extracts of ZA have reported strong anti-inflammatory and anti-oxidant activities, but no scientific report is available on its efficacy in intestinal inflammatory disorders like ulcerative colitis. Aim of the study: The overall objective of our study was to evaluate the anti-inflammatory potency of hydro-ethanolic extract of Zanthoxylum alatum seed (ZAHA) using both in-vitro NF-κB-luciferase translocation assay and in-vivo stress aggravated dextran sodium sulfate (DSS)-induced ulcerative colitis model. Materials and methods: The in-vitro anti-inflammatory effect of ZAHA extract was evaluated by luciferase assay in HEK293 cells. Parameters such as body weights, behavioural, colonoscopy, colon lengths and spleen weights were measured and recorded in stress aggravated DSS-induced colitis model in C57BL/6 mice. Biochemical, histological and immunoblot analysis in the colon tissues were determined to prove its anti-inflammatory and anti-oxidant activities. Characterization of the extract was done by LC-MS/MS study. Results: Initial in vitro NF-κB-luciferase translocation assay showed that the hydroalcoholic extract of ZA (ZAHA) showed potent inhibitory activity for NF-κB translocation by TNF-α stimulation and hence this particular extract was further evaluated in stress aggravated DSS-induced ulcerative colitis model in C57BL/6 mice. Treatment of ZAHA for two weeks at a dose of 200 mg/kg significantly ameliorated the stress aggravated DSS-induced colitis in mice. Histological alterations, infiltration of inflammatory cells, and the levels of IL-1β, IL-6, TNF-α in colon tissue and serum samples were significantly decreased in ZAHA treatment groups compared to the stress aggravated DSS induced colitis animals. Moreover, the protein expressions of p-NF-κB, p-IκBα, p-STAT3, COX-2, and TNF-α were significantly reduced in colon tissues of ZAHA treated groups and also increased anti-oxidant markers like SOD-1, Nrf2 significantly when compared with disease control group. Characterization of the extract further by LC-MS/MS revealed the presence of several active compounds which could be responsible for its anti-inflammatory activity. Conclusions: Thus from the above findings it can be concluded that ZAHA ameliorates stress aggravated DSS-induced ulcerative colitis due to its anti-inflammatory and anti-oxidant activity. Graphical abstract: Image 1